PERANCANGAN DAN IMPLEMENTASI JARINGAN VPN MENGGUNAKAN VPLS (Information Technology and Telematics, 2014)
Abstract− An internet ISP(internet service provider) is company that provides service for accessing, using, or participating in the internet. Internet service providers may be organized in varous forms, such as commercial, community – owned, non-profit, or otherwise privately owned.internet servie typically provided by ISPs include internet access, internet transit, domain name regristration, web hosting, collocation. PT. Data Utama Dinamika is one give a good service for their customer that’s why they OSPF (Open Shortest Path First) and the connection spread to customer using VPN (Virtual Private Network) with VPLS based on OSPF and MPLS (Multiprotocol Label Switching) infrastructure. And VPN will makes the connections direct to the customer. In this study, the writer used some steps; the fist is design the connection and second is implementation in routers, user pass, router id, OSPF, MPLS, and VPN which run on VPLS’s methods. And the result is connection using OSPF, MPLS and VPLS which applied in VPN make it running well and it will search for another path where one of it lost. Keyword − Network VPN, OSPF, MPLS, VPLS